2022
DOI: 10.1002/acr.24525
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic Muscle Activity and Three‐Dimensional Scapular Kinematics in Patients With Multidirectional Shoulder Instability: A Study in the Hypermobile Type of the Ehlers‐Danlos Syndrome and the Hypermobility Spectrum Disorders

Abstract: Objective To investigate differences in electromyography (EMG), muscle activity, and scapular kinematics during elevation in the scapular plane between healthy controls, participants with multidirectional shoulder laxity (MDL), and patients with multidirectional shoulder instability (MDI) who are diagnosed with hypermobile Ehlers‐Danlos syndrome (hEDS) or hypermobility spectrum disorder (HSD). Methods Twenty‐seven women with hEDS/HSD and MDI, 27 female healthy control subjects, and 28 female subjects with MDL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…When the history of presenting complaint was analyzed in this review, patients were deemed symptomatic when they presented with either pain, instability and/or subluxation, and/or dislocation in 45 studies ( 1 , 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the history of presenting complaint was analyzed in this review, patients were deemed symptomatic when they presented with either pain, instability and/or subluxation, and/or dislocation in 45 studies ( 1 , 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-four studies explicitly excluded voluntary dislocators ( 1 , 19 , 21 , 22 , 23 , 28 , 36 , 37 , 42 , 43 , 44 , 45 , 48 , 50 , 55 , 59 , 61 , 62 , 67 , 68 , 69 , 70 , 71 , 73 ), while the rest of the studies did not.…”
Section: Resultsmentioning
confidence: 99%
“…Acknowledging the fact that patients with HSD and shoulder symptoms have different clinical profiles (eg, regarding symptoms and coexistent shoulder diagnoses),25 the difference in exercise programmes may be of importance when choosing which exercises the patient should use. There is moderate evidence for altered muscle activity and altered humeral and scapular kinematics in individuals with multidirectional instability with and without HSD that could be addressed in the rehabilitation 42 43. Closed kinetic chain shoulder abduction exercises may enable full range of motion earlier in rehabilitation programmes, and open kinetic chain shoulder abduction exercises are required to facilitate the stabilising role of the rotator cuff and axioscapular muscles through daily function 44.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, four out of five people with HSD experience symptoms in the shoulder joint3 9–11 with profound consequences in daily life 4 5. Recent studies have reported altered scapular kinematics, imbalanced electromyographic scapular muscle activity and increased humeral head translation in patients with HSD and multidirectional shoulder instability 12 13. However, there is no gold standard management, and no studies have focused on treatments of the shoulder for this patient group 14–17.…”
Section: Introductionmentioning
confidence: 99%
“… 4 5 Recent studies have reported altered scapular kinematics, imbalanced electromyographic scapular muscle activity and increased humeral head translation in patients with HSD and multidirectional shoulder instability. 12 13 However, there is no gold standard management, and no studies have focused on treatments of the shoulder for this patient group. 14–17 Generally, an important and effective component of exercise interventions for persistent shoulder complaints—such as rotator cuff tendinopathy and anterior or multidirectional glenohumeral instability—aims to improve the function of the scapular stabilising muscles and rotator cuff muscles.…”
Section: Introductionmentioning
confidence: 99%